Gambaran Kondisi Psikologis dan Coping Stres Staf Klinik IPWL BNN RI dalam Melayani Klien Penyalahgunaan Narkoba - Akbar, Rizky; Satria, Muhammad Daffa; Rahmania, Tia (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The number of drug users in Indonesia tends to increase every year, which leads to a rise in the number of cases that need to be handled by various related institutions, including the clinics of the Compulsory Reporting Institution (IPWL) of BNN RI. This study aims to describe the psychological condition and stress coping strategies used by the staff of IPWL BNN RI clinics in dealing with work pressures while serving clients with drug abuse problems. A qualitative approach with a phenomenological method was used to explore the staff’s subjective experiences regarding work-related stress and how they cope with it. Data were collected through in-depth interviews with two subjects and two informants who are clinic staff members. The results of the study indicate that the primary sources of stress stem from workload and difficult client demands. The staff employ two main coping strategies, namely emotion-focused coping and problem-focused coping. Although the stress experienced is quite significant, both subjects are able to manage it well, ensuring that it does not affect their overall performance.